Atribuição inequívoca de deslocamentos químicos de RMN de ¹H e 13C de plumierídeo isolado da Allamanda cathartica Complete assignments of chemical shifts of the hydrogen and carbon-13 atoms of plumieride isolated from Allamanda cathartica - Angela Malheiros; Ivânia T. A. Schuquel; Gentil José Vidotti (Química Nova, 1997)
There are NMR data of ¹H and 13C of the iridoid plumieride, but controversy related to the assignments of the protons H-3 or H-10 and carbons C-6 or C-7 and C-3 or C-10 are described in the literature. There are a little discussion regarding to the resonance assignment of protons of the glycoside unity. Analysis based on 2D shift correlated NMR spectra (COSY, HETCOR, HETCORLR) and NOE difference ¹H NMR spectra allowed to assign unambigously the chemical shift of ¹H and 13C of plumieride which has been found in the literature with non coincident values.